An Insight into Recombination with Enterovirus Species C and Nucleotide G-480 Reversion from the Viewpoint of Neurovirulence of Vaccine-Derived Polioviruses - Zhang, Yong (Sci Rep, 2015)
A poliomyelitis outbreak caused by type 1 circulating vaccine-derived polioviruses (cVDPVs) was identified in China in 2004. Six independent cVDPVs (eight isolates) could be grouped into a single cluster with pathways of divergence different from a single cVDPV progenitor, which circulated and evolved into both a highly neurovirulent lineage and a less neurovirulent lineage. They were as neurovirulent as the wild type 1 Mahoney strain, recombination was absent, and their nucleotide 480-G was identical to that of the Sabin strain. The Guizhou/China cVDPV strains shared 4 amino acid replacements in the NAg sites: 3 located at the BC loop, which may underlie the aberrant results of the ELISA intratypic differentiation (ITD) test. The complete ORF tree diverged into two main branches from a common ancestral infection estimated to have occurred in about mid-September 2003, nine months before the appearance of the VDPV case, which indicated recently evolved VDPV. Further, recombination with species C enteroviruses may indicate the presence and density of these enteroviruses in the population and prolonged virus circulation in the community. The aforementioned cVDPVs has important implications in the global initiative to eradicate polio: high quality surveillance permitted earliest detection and response.